PROBLEMS OF TEACHING THE SECTION OF SYNTAX IN PRIMARY GRADES - Yakhshiyeva Latofat (Journals Park Publishing, 2023)
This article talks about the problems of learning and teaching syntax elements in elementary grades. Also, the system of placing materials in classes was analyzed. It is written about the conditions and problems of students' formation of basic syntactic concepts.
Keywords: syntax, elementary grades, sentences, topics, morphology, phonetics, grammar, students, sentence fragments, mother tongue.